Unfavorable food consumption in children up to school entry age: results from the nationwide German KiESEL study - Spiegler, Clarissa; Jansen, Sara; Burgard, Leonie; Wittig, Friederike; Brettschneider, Anna-Kristin; Schlune, Andrea; Heuer, Thorsten; Straßburg, Andrea; Roser, Silvia; Storcksdieck Genannt Bonsmann, Stefan; Ensenauer, Regina (Frontiers in Nutrition, 2024)
Introduction: Evidence points towards the early life being crucial for preventing nutrition-related diseases. As promotion of healthier food preferences in toddlerhood and preschool age might still modulate the trajectories of disease risk, understanding diet in these age groups is necessary. The objective was to analyze food consumption and diet quality of 1-5-year-old children living in Germany in relation to age and sex. Methods: Data from 890 children, a subsample of the representative, cross-sectional Children's Nutrition Survey to Record Food Consumption (KiESEL) conducted by the German Federal Institute for Risk Assessment in 2014-2017, were analyzed. Dietary data were collected using food records (3 consecutive plus 1 independent day). Diet quality was evaluated against the German food-based dietary guidelines (FBDG). Results: Consumption of unfavorable foods (e.g. sweets, soft drinks) exceeded the recommended maximum of 10 % of energy intake (E%) by a multiple in all age and sex groups (medians: 24.8 E%-35.8 E%). Preschoolers consumed more unfavorable foods than toddlers and boys more than girls. More than half of the children exceeded the recommendation for meat intake (medians: 2.3-3.2 % of the total food consumption (%TFC) vs. 2 %TFC), especially preschoolers. In nearly all children, vegetable consumption was too low (medians: 4.2-4.5 %TFC vs. 12 %TFC). Also, milk/milk product consumption was below recommendations, more so in preschoolers (median: 12.0 %TFC ♂, 11. %TFC ♀ vs. 18 %TFC) than in toddlers (median: 16.1 %TFC ♂, 19.6 %TFC ♀). In toddlers and preschoolers with overweight or obesity, adherence to dietary recommendations of these food groups was largely similar to that of the total sample. Overall, 5-year-olds showed an unhealthier dietary pattern than 1-year-olds, which already emerged at age 2 years and became more evident at age 3 years. Discussion: An adverse dietary pattern arises and even deteriorates at a very young age, showing sex-specific aspects. High attention from public health and research needs to be given to toddlerhood and even earlier life phases, e.g., to develop more age-specific FBDGs, aiming at reducing unhealthy food consumption.